The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31269/triplec.v19i1.1206
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Marxist Political Economy Critique of Migration and the Media

Abstract: The global outbreak of COVID-19 has exposed varied ways that systemic inequality shapes people’s lives. This article pays particular attention to migrant populations. While mainstream media and political discourse tend to construct migration as a problem to be addressed or even the cause of social problems, the article contends that migration should be understood as an immanent part of capitalist uneven development, entwined with patriarchy and colonialism. The post-modern approach within media and communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…To boost the economic gains and their divine profits, capital owners demanded what is called liberal immigration policies to promote labour migration, as Rey indicated that capitalism is the root cause of migration (Gerold-Scheepers & Van Binsbergen, 1978, p. 28). The uneven development, which was initiated by the First World countries as a consequence of colonial rule (Yin, 2021;Gidwani & Sivaramakrishnan, 2003, p. 188;Hollifield, 1992, p. 571), has resulted in today's migratory flows.…”
Section: Discussion: Diversity or Exploitation?mentioning
confidence: 99%
“…To boost the economic gains and their divine profits, capital owners demanded what is called liberal immigration policies to promote labour migration, as Rey indicated that capitalism is the root cause of migration (Gerold-Scheepers & Van Binsbergen, 1978, p. 28). The uneven development, which was initiated by the First World countries as a consequence of colonial rule (Yin, 2021;Gidwani & Sivaramakrishnan, 2003, p. 188;Hollifield, 1992, p. 571), has resulted in today's migratory flows.…”
Section: Discussion: Diversity or Exploitation?mentioning
confidence: 99%